2009
DOI: 10.1016/j.jaerosci.2008.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Production of equal sized atomic clusters by a hot wire

Abstract: A resistively heated metal wire is shown to be a source of charged atomic clusters consisting of only a few atoms. They are size classified with a differential mobility analyzer, and their relative abundance is determined as a function of size. Ag n K + clusters are obtained from wires containing silver with traces of potassium to provide the electric charge. First principles calculations reveal that the abundance observed can be fully explained by the energetic and chemical stability of the neutral cluster an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…The observation of dominant peaks, corresponding to clusters consisting of odd number of atoms, in our measurements is consistent with cluster stability calculations available in literature (Peineke et al 2009). Previous studies have shown that even-numbered neutral silver clusters show enhanced chemical stability due to electron pairing.…”
Section: Results and Discussion Silver Cluster: Identification Of Clusupporting
confidence: 92%
See 1 more Smart Citation
“…The observation of dominant peaks, corresponding to clusters consisting of odd number of atoms, in our measurements is consistent with cluster stability calculations available in literature (Peineke et al 2009). Previous studies have shown that even-numbered neutral silver clusters show enhanced chemical stability due to electron pairing.…”
Section: Results and Discussion Silver Cluster: Identification Of Clusupporting
confidence: 92%
“…Previous studies have shown that even-numbered neutral silver clusters show enhanced chemical stability due to electron pairing. Meanwhile, for charged clusters, electron pairing occurs when they consist of odd numbers of atoms (Yannouleas and Landman 1995;Bouwen et al 1999;Schmidt et al 2003;Peineke et al 2009). Higher chemical stability leads to lower sensitivity to impurities and thus, more abundance in the measured distributions.…”
Section: Results and Discussion Silver Cluster: Identification Of Clumentioning
confidence: 99%
“…() referred to temperatures exceeding 1000°C. More recently, studies of atomic cluster emissions from glowing wires (Fernandez de la Moya et al., ; Peineke et al., , ) show that emission of atomic clusters is a function of the melting temperature T m of the wire and begins to increase when temperatures approach T m . For most metals, T m is in the range of 1000–2000°C (for iron it is 1811°C).…”
Section: Discussionmentioning
confidence: 99%
“…The Glowing wire generator (GWG) where material is evaporated from resistively heated wire and subsequently quenched by gas stream has been introduced by Schmidt-Ott et al (1980). The main advantage of this method is that it offers a precise control over contamination and generated aerosols have sizes in nanometer range (Peineke et al 2009). Another feature of production of nanoparticle aerosols using this method is significantly higher number emission rates which make them suitable to be used for specific purposes such as validation of coagulation-based aerosol evolution models.…”
Section: Introductionmentioning
confidence: 99%